2010
DOI: 10.1080/02640414.2010.492229
|View full text |Cite
|
Sign up to set email alerts
|

Gender and age inequalities in regular sports participation: A cross-national study of 25 European countries

Abstract: This article provides a unique opportunity to compare gender inequalities in sports participation across Europe, and the extent to which this varies by age using large, cross-sections of the population. The Eurobarometer Survey 62.0 (carried out in 2004 at the request of the European Commission and covering the adult population of 25 European member states, N = 23,909) was used to analyse differences in regular sports participation by gender and by age in the different countries. For the majority of countries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
84
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 24 publications
12
84
0
5
Order By: Relevance
“…8 In the Health Survey for England, 9 which was another long-term cross-sectional study, participation was stable at about 41% in men aged 16 years or older from 1997 to 2006. In women aged 16 years or older, participation ranged from 31% to 34% in 1997-2006.9 The Eurobarometer study, 10 which assessed participation in 25 countries, concluded that "for the majority of countries, the occurrence of regular (once or more per week) sporting activity was less than 40%". 10 In Australia, 48% of adults reported playing sport in a survey three or more times a week.…”
Section: Rates Of Participation In Sports and Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…8 In the Health Survey for England, 9 which was another long-term cross-sectional study, participation was stable at about 41% in men aged 16 years or older from 1997 to 2006. In women aged 16 years or older, participation ranged from 31% to 34% in 1997-2006.9 The Eurobarometer study, 10 which assessed participation in 25 countries, concluded that "for the majority of countries, the occurrence of regular (once or more per week) sporting activity was less than 40%". 10 In Australia, 48% of adults reported playing sport in a survey three or more times a week.…”
Section: Rates Of Participation In Sports and Exercisementioning
confidence: 99%
“…In women aged 16 years or older, participation ranged from 31% to 34% in 1997-2006.9 The Eurobarometer study, 10 which assessed participation in 25 countries, concluded that "for the majority of countries, the occurrence of regular (once or more per week) sporting activity was less than 40%". 10 In Australia, 48% of adults reported playing sport in a survey three or more times a week. 11 Of the sport reported in that survey, organized sport only represented a fi fth of the total sport.…”
Section: Rates Of Participation In Sports and Exercisementioning
confidence: 99%
“…[10][11][12] Another study, this performed in 2010, involving the adult population of 25 Member States of the European Union (n=23,909), showed that in France, Latvia, UK, Belgium, Spain, Netherlands and Greece, men aged 18 to 34 years of age were more likely to participate in recreational sport, when compared to women of the same age and men with 55 years or more. 13 In Australia, in the period from 2001 to 2010, for both sexes, participation in recreational sport was higher among individuals from 15 to 34 years when compared to older age groups. 14 In general, these surveys have provided evidence that participation in recreational PA decreases with the increase of age.…”
Section: Introductionmentioning
confidence: 99%
“…These currently unanswered questions are important since it is well known that different types of sporting activities are expected to have different organisational features and aspects of practice, which may affect their impact on the individual (Downward et al 2009). It is also well known that the type and intensity of sports related activities vary considerably over age and across genders (Van Tuyckom, et al 2010;Breuer and Wicker, 2009;Breuer and Wicker, 2008;Kay, 2003). To address these questions a 1 See also the 2007 White Paper on Sports by the European Commission (http://ec.europa.eu/sport/white-paper/whitepaper_en.htm; accessed 12/11/2014).…”
Section: Introductionmentioning
confidence: 99%